2016
DOI: 10.1155/2016/8501637
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Nutritional and Bioactive Properties of Aerial Parts of Snake Gourd (Trichosanthes cucumerinaLinn.)

Abstract: The present investigation was carried out to determine the nutritional and functional properties of T. cucumerina. Water extracts of freeze dried flowers, fruits, and leaves of T. cucumerina were evaluated for their total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity, α-amylase inhibitory activity, and fiber and mineral contents. Antioxidant activity, TPC, and TFC were significantly higher (P ≤ 0.05) in leaves than in flowers and fruits. A significant linear correlation was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
2
10
0
Order By: Relevance
“…Using the squashes and gourds as the fat substitute did not change the protein content compared to the control, probably due to the low protein content of the varieties of squashes and gourds tested (Rahman et al, 2008). Among all, SGBP had the highest value (13.14%), which in agreement with Liyanage et al (2016) who reported that the snake gourd has a high protein content, however, the protein values in the patties were still in the range observed in commercial chicken burgers (Ramadhan et al, 2011). The use of squashes and gourds as fat substitutes significantly decreased (p < 0.05) the fat content of the buffalo patties (0.70-2.05%) compared to the control (7.90%).…”
Section: Proximate Compositionsupporting
confidence: 86%
“…Using the squashes and gourds as the fat substitute did not change the protein content compared to the control, probably due to the low protein content of the varieties of squashes and gourds tested (Rahman et al, 2008). Among all, SGBP had the highest value (13.14%), which in agreement with Liyanage et al (2016) who reported that the snake gourd has a high protein content, however, the protein values in the patties were still in the range observed in commercial chicken burgers (Ramadhan et al, 2011). The use of squashes and gourds as fat substitutes significantly decreased (p < 0.05) the fat content of the buffalo patties (0.70-2.05%) compared to the control (7.90%).…”
Section: Proximate Compositionsupporting
confidence: 86%
“…This species is commonly called viper gourd, snake tomato, or long tomato, and has several synonyms (e.g., Trichosanthes cucumerina L.). Snake gourd originated in India or the Indo-Malayan region in tropical Asia 3,4 and is widely distributed in Asian countries [5][6][7] . Its green, tender stems, leaves, and fruits are consumed as edible vegetables 2,6 , which have high nutritional value, because they are rich in vitamins, essential minerals, dietary fiber, and other nutrients, and are a wholesome, healthy addition to diets 7,8 .…”
Section: Introductionmentioning
confidence: 99%
“…They reported that TPC of fruits decreased during development, while the flavonoids increased from 0.683 to 3.37 mg/g fresh weight. But Liyanage et al (2016) reported that TPC and TFC were higher in flower than fruits in aerial parts of snake gourd. We all well know that flavonoids comprise a group of many compounds such as flavones, flavonols, flavanones, flavanonols, flavonols, catechins, anthocyanins and chalcones, along with carotenoids, and they are responsible for the vivid colors in fruits and vegetables (Panche et al, 2016).…”
Section: Resultsmentioning
confidence: 97%